Behavioral stability of alcohol consumption and socio‐demographic correlates of change among a nationally representative cohort of US adults. (28th August 2022) - Puka, Klajdi; Buckley, Charlotte; Mulia, Nina; Purshouse, Robin C.; Lasserre, Aurélie M.; Kerr, William; Rehm, Jürgen; Probst, Charlotte
Abstract: Aims: To estimate the probability of transitioning between different categories of alcohol use (drinking states) among a nationally representative cohort of United States (US) adults and to identify the effects of socio‐demographic characteristics on those transitions. Design, setting and participants: Secondary analysis of data from the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC), a prospective cohort study conducted in 2001–02 and 2004–05; a US nation‐wide, population‐based study. Participants included 34 165 adults (mean age = 45.1 years, standard deviation = 17.3; 52% women). Measurements: Alcohol use was self‐reported and categorized based on the grams consumed per day: (1) non‐drinker (no drinks in past 12 months), (2) category I (women = ≤ 20; men = ≤ 40), (3) category II (women = 21–40; men = 41–60) and (4) category III (women = ≥ 41; men = ≥ 61). Multi‐state Markov models estimated the probability of transitioning between drinking states, conditioned on age, sex, race/ethnicity and educational attainment. Analyses were repeated with alcohol use categorized based on the frequency of heavy episodic drinking. Findings: The highest transition probabilities were observed for staying in the same state; after 1 year, the probability of remaining in the same state was 90.1% [95% confidence interval (CI) = 89.7%, 90.5%] for non‐drinkers, 90.2% (95% CI = 89.9%, 90.5%) for category I, 31.8% (95% CI = 29.7, 33.9%) category II and 52.2% (95% CI = 46.0, 58.5%) for category III. Women, older adults, and non‐Hispanic Other adults were less likely to transition between drinking states, including transitions to lower use. Adults with lower educational attainment were more likely to transition between drinking states; however, they were also less likely to transition out of the 'weekly HED' category. Black adults were more likely to transition into or stay in higher use categories, whereas Hispanic/Latinx adults were largely similar to White adults. Conclusions: In this study of alcohol transition probabilities, some demographic subgroups appeared more likely to transition into or persist in higher alcohol consumption states.